On some commensal anomuran and brachyuran crabs (Crustacea: Decapoda) off Visakhapatnam, Northwestern Bay of Bengal - Silambarasan, Krishnan; Kar, Annada Bhusan; Prasad, Gummadi Venkata Ankineedu; Pattnayak, Sujit Kumar; Das, Pratyush; Reddy, Dwarampudi Bhami; Ramalingam, Lakshmana Perumal (Zootaxa, 2023)
Commensal anomuran and brachyuran crabs were collected from extensive exploratory surveys on rocky areas where soft corals, sea anemones and sponges are found off the Visakhapatnam coast. The present study includes nine species of commensal decapod crustaceans, comprising four porcellanid crabs (Petrolisthes lamarckii (Leach, 1820), Porcellanella triloba White, 1852, Polyonyx hendersoni Southwell, 1909 and Pisidia gordoni (Johnson, 1970)), one squat lobster (Allogalathea elegans (Adams, 1847) and four brachyuran crabs (Dorippoides facchino (Herbst, 1785), Quadrella coronata Dana, 1852, Quadrella maculosa Alcock, 1898 and Sphenomerides trapezioides (Wood-Mason & Alcock, 1891). Allogalathea elegans, Polyonyx hendersoni, Pisidia gordoni, Quadrella coronata and Quadrella maculosa are new records from off Visakhapatnam. The porcellanid crabs are associated with the sea pen Pteroeides esperi, desmosponges and black soft corals Antipathes sp. whereas the squat lobster was associated with the soft coral Dendronephthya sp. The brachyuran crabs were observed in association with Antipathes sp. Here, we provide details on the morphology, distribution, habitat and commensalism of decapod crustaceans studied.